Enforcement of Epoxy with Silica Fume and Carbon Fiber - Amer Hameed Majeed (Tikrit Journal of Engineering Sciences, 2018)
A composite material has been prepared using epoxy resin as a matrix, reinforced with silica fume, carbon fiber, and their hybrid (mixture of silica fume and carbon fiber). Samples were prepared in a fabricated mold with dimensions according to the American Standards for Testing and Materials (ASTM). The additions of silica fume, carbon fiber, and mixture of them were with weight ratios of 0.5, 1, 1.5, 2, 2.5 and 3 wt.%. Properties of this composite material are determined; hardness, compression, and ultrasonic. The results showed that the mechanical properties increases with increasing of silica fume ratio up to 2 wt.%, and for higher than of 2 wt.% they were decrease, whereas the addition of carbon fiber and mixture of carbon fiber with silica fume powder correspondingly enhances the properties up to 2 wt.% and fixed on its values.